Philippine medical thesaurus on anatomy animal structures and respiratory system in Iluko - Lovina, Paul Michael B.; Tarlit, Rodolfo Y. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 2005)
This study is a part of the Philippine Medical Thesaurus project. It aims to build an informant tool particularly, a medical thesaurus in Iluko to help bridge the language gap between medical professionals and their patients. The top-down approach and domain analysis were used to build the thesaurus. It used informants consisted of medical and non-medical professionals who are native speakers of Iluko from Baguio City to validate the translated medical terms. The thesaurus was patterned after the Unified Medical Language System (UMLS) of the US National Library of Medicine.
The terms were downloaded from the Medical Subject Headings (MeSH) (Category A-anatomy Subcategories A13 Animal Structures and A4 Respiratory system) and were translated into Iluko. In building the thesaurus, the researcher adhered to ISO 2788: Guidelines for the establishment and development of monolingual thesauri (1986) and ISO 5964: Guidelines for the establishment and development of multilingual thesauri (1985). This ensures conformity amongst all the other researchers building the thesaurus in Iluko or in other languages.
The researcher was able to get 66 translations out of 94 (MeSH terms. After the relationships (BT, NT and RT) between the terms were determined, the terms were then compiled alphabetically. Also, the pronunciation of the terms was provided in the CD-ROM accompanying this study.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Subject headings. Ilocano -- Medicine; Subject headings, Ilocano -- Respiratory System; Ilocano language -- Medical Ilocano